RPM 2021
DOI: 10.21926/rpm.2101007
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Nanomaterials in Preventative and Restorative Dentistry

Abstract: To date, many studies have examined the development and use of novel materials, enhancing the performance of existing dental composites and improving methods for restoring tooth structure. In recent years, nanotechnology-based techniques have been used to develop a variety of nanomaterial-based dental products aimed at conservative dentistry applications. These new nanomaterial-based materials offer improved physicochemical and mechanical properties, combined with enhanced aesthetics that makes them superior r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 253 publications
(290 reference statements)
0
3
0
Order By: Relevance
“…It has been demonstrated that the addition of alumina, hydroxyapatite, silica, or zirconium nanoparticles as fillers to the organic matrix increases the resistance to the masticatory stress and the wear resistance during mastication [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the addition of alumina, hydroxyapatite, silica, or zirconium nanoparticles as fillers to the organic matrix increases the resistance to the masticatory stress and the wear resistance during mastication [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although graphene is a hydrophobic material, GO is considered hydrophilic as it contains oxygen in its functional groups [14]. GO is used in a variety of research experiments, for example, for teeth whitening, antimicrobial activity, dental erogenous, dental implants, tooth pain, and drug delivery in a specific location [15].…”
Section: Introductionmentioning
confidence: 99%
“…Composites and nano-composites as dental polymers have recently been developed [17]. With the integration of nanotechnology and engineering abilities in the dentistry field, better materials for dental applications have been developed [18].…”
mentioning
confidence: 99%